90.9k views
5 votes
Using exponet rules,simplify each exspression. leave no negitive exponets in your awnser

Using exponet rules,simplify each exspression. leave no negitive exponets in your-example-1
User Pault
by
5.4k points

1 Answer

0 votes

We have the expression:


3^3\cdot3^5\cdot((1)/(3))^2=(3\cdot3\cdot(1)/(3))^(3+5+2)=3^(10)

You operate the bases and elevate at the sum of the exponent [As shown in the procedure] in this particular case.

***

When you use a power, you multiply the number by itself the number of times it is stated by the exponent, for example:


((1)/(3))^2=(1)/(3)\cdot(1)/(3)=(1)/(9)

Or:


((1)/(3))^5=(1)/(3)\cdot(1)/(3)\cdot(1)/(3)\cdot(1)/(3)\cdot(1)/(3)=(1)/(243)

User CoolestNerdIII
by
5.4k points